Modeling and Analysis in Frequency of the UWB Channel with Lognormal Statistics for MB-OFDM Systems (2009)
In this paper, the ultra-wideband channel with multiband orthogonal frequency division multiplexing (MB-OFDM-UWB) is analyzed in the frequency domain. For UWB channels with lognormal small-scale fading in time domain, we obtain closed analytical expressions for the parameters that model the sub-carrier fading statistics of MB-OFDM-UWB system, and we show that magnitudes of the channel frequency responses of each subcarrier can be approximated by a Nakagami-m random variable, where the fading parameter (m), mean power Omega and the correlation, rhoij are expressed in terms of the following parameters: arrival time of the clusters, inter-arrival time of the rays inside the clusters, and power decay constants of the rays and clusters.